2016
DOI: 10.1261/rna.056317.116
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of the OCC-1 gene generates three splice variants and a novel exonic microRNA, which regulate the Wnt signaling pathway

Abstract: The Wnt signaling pathway is hyperactivated in most colorectal cancers (CRC). Finding new regulators of this pathway represents the potential for cancer diagnosis or treatment. OCC-1 was initially reported as an up-regulated gene in colon carcinoma, without knowing its mechanism of action. Here, two novel transcript variants and an exonic microRNA that originated from the OCC-1 gene are reported, showing positive effects on Wnt activity. Up-regulation of the known OCC-1 variant (assigned as OCC-1A/B) was limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…The lack of OCC-1 polypeptide, in some extent, may due to the high GC-content of OCC-1 5′UTR and the highly stable hairpin structure around the initial codon, which would lower the translational efficiency dramatically ( 38 ). In addition, a novel noncoding OCC-1 splice variant (OCC-1D) was also discovered in CRC, in which a 60-nucleotide RNA fragment containing the initial codon of OCC-1 ORF was spliced out ( 39 ). Thus, we supposed that OCC-1 RNA has noncoding function independent of its polypeptide product in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of OCC-1 polypeptide, in some extent, may due to the high GC-content of OCC-1 5′UTR and the highly stable hairpin structure around the initial codon, which would lower the translational efficiency dramatically ( 38 ). In addition, a novel noncoding OCC-1 splice variant (OCC-1D) was also discovered in CRC, in which a 60-nucleotide RNA fragment containing the initial codon of OCC-1 ORF was spliced out ( 39 ). Thus, we supposed that OCC-1 RNA has noncoding function independent of its polypeptide product in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…In COPD, up-regulation of follistatin may represent a compensatory mechanism aiming to sustain muscle mass in response to energy deficit. The only protein-coding gene to show a large magnitude reduction in abundance was C12orf75 , which binds the insulin receptor substrate 4 protein (IRS4) to promote insulin signalling in rat hypothalamic and human embryonic kidney cells 28 , and undergoes alternative splicing with products differentially regulating Wnt signalling 29 . This may similarly be a mechanism co-ordinating energy status and muscle growth/regeneration in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some of these signaling pathways are involved in the development of colorectal cancer, such as the Wnt and Ras signaling pathways. [ 25 , 26 ] Based on the previous research, the identification of some tumor-related signaling pathways, including the p53, Wnt, and TGF-β signaling pathways, which were mapped to some pathways in CRC, such as cell cycle and survival, [ 27 ] showed that microRNAs and their target genes were directly involved in the biological process of CRC and that CRC cell carcinogenesis was indirectly inhibited by the cell signaling pathways in different stages of CRC. Therefore, intervening in these signaling pathways may provide a new method for individualized treatment for and diagnosis of CRC.…”
Section: Discussionmentioning
confidence: 99%